2009
DOI: 10.1140/epjd/e2009-00213-7
|View full text |Cite
|
Sign up to set email alerts
|

Physisorption kinetics of electrons at plasma boundaries

Abstract: Abstract. Plasma-boundaries floating in an ionized gas are usually negatively charged. They accumulate electrons more efficiently than ions leading to the formation of a quasi-stationary electron film at the boundaries. We propose to interpret the build-up of surface charges at inert plasma boundaries, where other surface modifications, for instance, implantation of particles and reconstruction or destruction of the surface due to impact of high energy particles can be neglected, as a physisorption process in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 79 publications
0
32
0
Order By: Relevance
“…Both parameters depend on the inelastic, that is, the dynamic interaction between the electron and the grain. As discussed in [30], a rigorous calculation of (sτ ) e has to be based on a microscopic model for the electron-grain interaction taking elementary excitations of the grain into account. Quantum-kinetic equations have then to be solved to obtain s e and τ e separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both parameters depend on the inelastic, that is, the dynamic interaction between the electron and the grain. As discussed in [30], a rigorous calculation of (sτ ) e has to be based on a microscopic model for the electron-grain interaction taking elementary excitations of the grain into account. Quantum-kinetic equations have then to be solved to obtain s e and τ e separately.…”
Section: Discussionmentioning
confidence: 99%
“…In principle the coupling to other elementary excitations of the grain (plasmons, electron-hole pairs, ...) can compensate for the lack of coupling to lattice vibrations but how efficient this coupling really is is not at all obvious. In a recent exploratory calculation we found, for instance, that the electron sticking coefficient at metallic boundaries arising from the coupling to internal electron-hole pairs is also extremely small, at least when the Coulomb interaction between an internal and an external electron is realistically screened [30].…”
Section: Elementary Surface Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, for high floating potentials ͑ f Ϸ −1 keV͒, Pavlů et al 19 found that the particle charge is limited by field emission of electrons, which strongly depends on the surface properties ͑material͒. Furthermore, Bronold et al 20 proposed a charging model that uses a quantum mechanical ansatz to describe the physisorption process of electrons at the particle surface. Here, the particle charge depends on the surface states of the material.…”
Section: Discussionmentioning
confidence: 99%
“…It is only until recently that we pointed out 39,40 that the charging of surfaces in contact with an ionized gas, as it occurs, for instance, in the interstellar medium, [41][42][43] in the upper atmosphere, 44 in dusty laboratory plasmas, 45,46 and in dielectrically bounded low-temperature plasmas, [47][48][49][50][51][52] could be perhaps microscopically understood as an electronic physisorption process.…”
Section: Introductionmentioning
confidence: 99%